Misperceiving Inequality - Vladimir Gimpelson; Daniel Treisman (Institute for the Study of Labor (IZA), 2015)
Since Aristotle, a vast literature has suggested that economic inequality has important political consequences. Higher inequality is thought to increase demand for government income redistribution in democracies and to discourage democratization and promote class conflict and revolution in dictatorships. Most such arguments crucially assume that ordinary people know how high inequality is, how it has been changing, and where they fit in the income distribution. Using a variety of large, cross-national surveys, we show that, in recent years, ordinary people have had little idea about such things. What they think they know is often wrong. Widespread ignorance and misperceptions of inequality emerge robustly, regardless of the data source, operationalization, and method of measurement. Moreover, we show that the perceived level of inequality and not the actual level correlates strongly with demand for redistribution and reported conflict between rich and poor. We suggest that most theories about political effects of inequality need to be either abandoned or reframed as theories about the effects of perceived inequality.
Keywords: D31; D63; D83; H24; H54; I30; 330; inequality; income distribution; biased perceptions; preferences for redistribution